7.0k views
0 votes
Solve the equation for x: 3(m+7)=6(m+2)

User Bakaburg
by
4.8k points

2 Answers

7 votes
3=m

Distribute 3 to (m+7) and distribute 6 to (m+2)
With that you end up with:
3m + 21 = 6m + 12
Subtract 3m from 6m
21=3m+12
Then subtract 12 from 21
9=3m
Divide by 3 in both sides
3=m
And that’s your answer!
User Pushpendra Kumar
by
5.2k points
2 votes

Answer:

3

Explanation:

There is no x in the equation, so I will assume solving for m

Distribute:

3m + 21 = 6m + 12

Subtract 3m and 12

3m = 9

Divide by 3

m = 3

User Jthorpe
by
4.6k points